Secondary ionization mass spectrometry analysis in petrochronology - Schmitt, Axel Karl; Vazquez, Jorge A. (Petrochronology, 2017)
The goal of petrochronology is to extract information about the rates and conditions at which rocks and magmas are transported through the Earth’s crust. Garnering this information from the rock record greatly benefits from integrating textural and compositional data with radiometric dating of accessory minerals. Length scales of crystal growth and diffusive transport in accessory minerals under realistic geologic conditions are typically in the range of 1-10’s of μm, and in some cases even substantially smaller, with zircon having among the lowest diffusion coefficients at a given temperature (e.g., Cherniak and Watson 2003). Intrinsic to the compartmentalization of geochemical and geochronologic information from intra-crystal domains is the requirement to determine accessory mineral compositions using techniques that sample at commensurate spatial scales so as to not convolute the geologic signals that are recorded within crystals, as may be the case with single grain or large grain fragment analysis by isotope dilution thermal ionization mass spectrometry (ID-TIMS; e.g., Schaltegger and Davies 2017, this volume; Schoene and Baxter 2017, this volume). Small crystals can also be difficult to extract by mineral separation techniques traditionally used in geochronology, which also lead to a loss of petrographic context. Secondary Ionization Mass Spectrometry, that is SIMS performed with an ion microprobe, is an analytical technique ideally suited to meet the high spatial resolution analysis requirements that are critical for petrochronology (Table 1). View this table: Table 1 Advantages and limitations of in-situ SIMS analysis for petrochronology in comparison with other isotope selective methods In SIMS, Lombardment of solid targets with an energetic ion beam removes atoms from the sample where primary ions are implanted into the target material to a depth of < 5-10 nm. Lateral resolution is controlled by primary ion beam dimensions (sub-μm to few 10’s of μm) with an upper limit set by the acceptance …